Effect of Salinity Adaptation Technique on Survival and Growth Rate of Patin Catfish, Pangasius sp. - Nirmala, K.; Lesmono, D.P.; Djokosetiyanto, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
This study was carried out to determine the effect of salinity adaptation techniques on growth and survival of patin catfish Pangasius sp. fry. Fry of 1.5-2.0 inch in length were reared in the water with different of the initial salinity of 1, 2, 3, 4 and 5 ppt. Salinity was then daily increased by duplicated the initial water salinity until fish died. The results of study showed that fry could survive by initial salinity adaptation of 1 ppt and then increasing the salinity by 1 ppt/day to reach 27 ppt. In the other treatments, all fry died after the salinity reach 18-25 ppt. Keywords: patin catfish, Pangasius, adaptation, salinity ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh teknik adaptasi salinitas terhadap pertumbuhan dan kelangsungan hidup benih ikan patin Pangasius sp. Benih patin ukuran 1,5-2 inci dipelihara pada salinitas awal berbeda, yaitu 1, 2, 3, 4 dan 5 ppt. Salinitas air pemeliharaan ditingkatkan kelipatan dari salinitas awal setiap hari hingga ikan mati. Hasil penelitian menunjukkan bahwa adaptasi salinitas awal 1 ppt dan peningkatan sebesar 1ppt/hari menyebabkan ikan dapat bertahan hidup sampai pada salinitas 27 ppt. Pada perlakuan lainnya, benih ikan mengalami kematian masal ketika salinitas mencapai 18-25 ppt. Kata kunci: ikan patin, Pangasius, adaptasi, salinitas